Fungal diversity of saprotrophic litter fungi in a Mediterranean maquis environment - Lunghini, D; Granito, V M; Di Lonardo, D P; Maggi, O; Persiani, A M (MYCOLOGIA, 2013)
Monospecific and mixed-leaf litters from plant species of Mediterranean maquis (Quercus ilex, Phillyrea angustifolia, Pistacia lentiscus, Cistus spp.) in an undisturbed area in southern Italy were studied with respect to the structure and composition of their decomposer fungal community over an incubation period of 403 d. The data matrix structure was analyzed by means of detrended correspondence analysis (DCA), while indicator species analysis (ISA) was used to determine the preferential association of species with a substrate, a succession phase and monospecific/mixed experimental conditions. The ecological nature of the gradient expressed by the DCA axes was investigated by means of experimental and main chemical leaf-litter variables. The litter mixture had non-additive effects on the decomposition process even though the fungal species richness of the mixed litter was considerably higher than that of the monospecific litter. Our findings highlight the occurrence of shifts in the fungal community during decomposition in response to changes in the substrate, such as those related to the cellulose content and lignin/N ratio.
Keywords: decomposition; fungal biodiversity; leaf-litter quality; Litter bags; Mediterranean maquis; monospecific/mixed litter

Studies on Mediterranean Hyphomycetes .3. Quadracaea mediterranea anam-gen and sp nov - Lunghini, D; Pinzari, F; Zucconi, L (MYCOTAXON, 1996)
Quadracaea mediterranea anam.-gen. et sp. nov., an hyphomycete recorded on leaves of Quercus ilex L. from central Italy, is described, discussed and illustrated, also by means of SEM.
Keywords: Endophragmi; Hyphomycetes; Quadracaea mediterranea